Comprehensive review of chromium deposition and poisoning of solid oxide fuel cells (SOFCs) cathode materials. (December 2020) - Zhou, Lingfeng; Mason, Jerry H.; Li, Wenyuan; Liu, Xingbo
Abstract: A solid oxide fuel cell (SOFC) is a clean and efficient energy conversion device. The development of intermediate-temperature SOFCs has made it preferable to use metallic interconnects (MICs) to greatly reduce the cost and significantly increase the efficiency compared to ceramic interconnect materials. However, gaseous chromium species will evaporate from the chromium-containing layer formed on the surface of commonly used MICs. Volatile chromium species have been shown to form solid deposits which poison the cathodes of SOFCs, causing drastic cell performance degradation and thereby limiting commercialization. In this review, we systematically summarize the status and progress of research on this topic and compare the variations in chromium poisoning phenomena under numerous SOFC operating conditions. Moreover, approaches to alleviate chromium poisoning are evaluated and discussed. Highlights: Data from over 450 chromium poisoning experiments from 78 different publications have been systematically documented. Effects of current density, temperature and humidity on chromium deposition are critically analyzed. Time of flight secondary ion mass spectrometry could be applied to investigate chromium quantities. Fundamental chromium deposition and poisoning mechanisms are deeply discussed. Effective approaches are comprehensively to alleviate Cr-poisoning.